Distribution of Camphor Monooxygenase Genes in Soil Bacteria - N. Ngadiman; Hikaru Suenaga; Masatoshi Goto; Kensuke Furukawa (Universitas Gadjah Mada, 2005)
In microbial degradation of camphor, the first step is oxidation by multiunit enzyme, camphor monooxygenase, encoded by cam genes (camA,B,C). Seven camphor-utilizing bacterial strains have been isolated from soil at various locations. CamA,B,C genes of Pseudomonas putida strain PpG1 and strain GF2001 were used as probes to explore their abundance in the camphor-utilizing bacteria. Southern analysis revealed that all of the cam genes of GF2001 could hybridize well to the SpeI-digested genomic DNA of strains tested, whereas PpG1 cam genes were not. This result suggested that the GF2001 type cam genes are widely distributed among the camphor- utilizing strains in the environment. Thus strain GF2001 and seven newly isolated strains share a common evolutionary origin.